2018
DOI: 10.7589/2017-09-236
|View full text |Cite
|
Sign up to set email alerts
|

SEROLOGIC SURVEY FOR SELECTED VIRAL AND BACTERIAL SWINE PATHOGENS IN COLOMBIAN COLLARED PECCARIES (PECARI TAJACU) AND FERAL PIGS (SUS SCROFA)

Abstract: In South America, wild populations of peccaries coexist with domestic and feral pigs, with poorly understood consequences. We captured 58 collared peccaries ( Pecari tajacu) and 15 feral pigs ( Sus scrofa) in locations of Colombia where coexistence of these species is known. Blood samples were tested for antibodies against four viral agents, classical swine fever virus (CSFV), Aujeszky's disease virus (ADV), porcine circovirus (PCV-2), and vesicular stomatitis virus (New Jersey and Indiana subtypes) and two ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In Mexico, two collared peccaries were positive for the Icterohaemorrhagie and Panama serogroups ((Luna-Alvarez, Moles-Cervantes, Torres- Barranca & Gual-Sill, 1996). In Colombia it was reported that 39 (78 %) free-living collared peccaries showed a high prevalence for serogroups Australis, Icterohaemorrhagiae, Grippotyphosa, Canicola, and Pomona (Montenegro et al, 2018). Thus, it is possible to indicate the participation of these animals as links in the epidemiological chain of the disease and, probably, the lower prevalence in this study may be associated with the better sanitary control offered to captive animals (8.33 %), differently from free-living ones.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, two collared peccaries were positive for the Icterohaemorrhagie and Panama serogroups ((Luna-Alvarez, Moles-Cervantes, Torres- Barranca & Gual-Sill, 1996). In Colombia it was reported that 39 (78 %) free-living collared peccaries showed a high prevalence for serogroups Australis, Icterohaemorrhagiae, Grippotyphosa, Canicola, and Pomona (Montenegro et al, 2018). Thus, it is possible to indicate the participation of these animals as links in the epidemiological chain of the disease and, probably, the lower prevalence in this study may be associated with the better sanitary control offered to captive animals (8.33 %), differently from free-living ones.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Leptospira spp. (78%) in collared peccaries was recently reported, the most frequent serovars are bratislava, grippotyphosa, icterohaemorrhagiae and pomona (Montenegro et al, 2018). Collared peccaries have also been found to harbour classical swine fever virus (5%), porcine circovirus type 2 (7%) and vesicular stomatitis (33%).…”
Section: Introductionmentioning
confidence: 90%
“…Collared peccaries have also been found to harbour classical swine fever virus (5%), porcine circovirus type 2 (7%) and vesicular stomatitis (33%). They also share pathogens with domestic and wild pigs (Sus scrofa) (Montenegro et al, 2018;Molina-Barrios et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance of pathogens in wild animals is crucial to understand the epidemiology of infectious diseases which can impact in both human and livestock health. Notably, peccaries and swine (domestic pigs and wild boars) share susceptibility to several important infectious agents as Classical Swine Fever virus and Leptospira (de Castro et al., 2014; Corn, Lee, Erickson, & Murphy, 1987; Montenegro et al., 2018). HEV, which is widely distributed in swine populations worldwide, has never been reported to infect peccaries.…”
Section: Introductionmentioning
confidence: 99%